What the f*ck just happened? : A study of the post-rape decision-making on safety, response and justice by adolescent girls in South Africa - Eichstedt, Anneke (Department of Public Law, 2025)
One in every three South African teenagers has experienced sexual violence but how they respond to their victimisation remains a paradoxical yet pivotal question. Teenagers must decide whether to seek (in)formal support following being raped, which has implications for their protection, health, and well-being. However, the role of adolescent rape survivors as decision-makers remains under-investigated. Therefore, this study aims to understand the multifaceted factors that influence the decision-making on safety, response, and the pursuit of justice by teenage girls following sexual victimisation. Drawing from interviews with female teenage survivors of sexual violence (n=40), caregivers of survivors (n=11), key informants working in the field of sexual violence (n=16), and adolescent peer educators (n=18), my primary research question examines the underlying ‘how' and ‘why' of the post-victimisation decision-making on safety, response, and justice by South African teenagers; and how Bourdieu's theoretical concepts of habitus, capital, field, and practice offer a novel framing for understanding their decision-making following sexual victimisation. Through the lens of Bourdieu's ‘Theory of Practice', I foreground the adolescent decision-maker and show that the context in which experiences are gained, tendencies are developed, and resources are acquired matters for how they respond to rape. The findings suggest that the teenagers' decisions are not made in a vacuum, isolated from the violence happening all the time, all around them. Growing up in some of South Africa's most violent and marginalised communities, they learn how to navigate crime, recognise sexual violence, seek safety, and cope with deficiencies in resources, which becomes the foundation for their decision-making following being raped. I argue that responding to dangerous situations has become a routinised practice for the young women, and that understanding their post-rape decisions requires paying attention to their everyday reality as a source of routine, socialising experiences, available support and monetary resources, sources of information, and recourseseeking options within their communities. None of these experiences and conditions alone sufficiently explains the decision-making, but it is the interplay between learning, support, information, resources, and safety provisions and response that explains how and why teens respond to their sexual victimisation